EFFECT OF DIGITAL INFLUENCERS IN BRAND RECOMMENDATIONS ON THE INSTAGRAM SOCIAL MEDIA PLATFORM ON BRAND ENGAGEMENT, BRAND EXPECTED VALUE AND PURCHASE INTENTION SCARLETT WHITENING - Dian Aulia Rahmah; Osa Omar Sharif (Jurnal Ekonomi, 2023)
This study aims to determine whether there is influence of Digital Influencers on Brand Engagement in Self-Concept, Brand Expect Value and Purchase Intention. The population of this study were followers of Scarlett Whitening's Instagram social media account using purposive sampling, which is a sample collection technique from non-probability sampling. The sample used in this study is at least 400 respondents. The method used is descriptive and causal analysis with quantitative methods and for collecting data through questionnaires. The data analysis technique in this study used Structural Equation Modeling (SEM) using SmartPLS software. Based on the results of the data analysis that has been obtained, it can be concluded that Perceived Influence has a positive and significant influence on Brand Engagement in Self-Concept, Brand Expect Value and Purchase Intention. Besides that, Brand Engagement in Self-Concept also has a positive and significant effect on Brand Expect Value and Purchase Intention. As well as the variables Perceived Influence and Brand Expect Value also have a positive and significant influence on Purchase Intention.